Service-Learning in Biochemstry Course: A Model to Improve the Problem-Solving Skills of Biology Education Students - Sukardi Abbas; Lintal Muna; Wirda Az. Umagap; Rosita Tabaika; Astuti Muh Amin (Postgraduate, University of Mataram, 2024)
Collaboration, communication, and problem-solving skills are becoming increasingly important in the modern workplace. Integration of learning activities, research, and community service was discovered to be an effective way to develop these abilities in students. The present study employed a mixed-methods sequential explanatory design to examine the effect of the service-learning model on seventeen college students. Observation, interview, and a problem-solving test were used to collect the data. The data were analyzed qualitatively and quantitatively. The quantitative data analysis was performed using the parametric pretest and post-test design. The results showed that participants’ problem-solving skills improved after being exposed to the service-learning model, indicated by the significance value of more than 0.05 in the non-parametric Wilcoxon test. Likewise, the qualitative analysis indicated that 95% of the participants considered the SL model effective in improving their problem-solving skills, especially the abilities to explore content, identify problems, solve the problems, and communicate scientific concepts.